OC-102 Coeliac disease, anti-inflammatory drugs or Helicobacter pylori are the most common identifiable causes of lymphocytic duodenosis. (28th May 2012) - Aziz, I; Evans, K E; Hopper, A D; Smillie, D M; Sanders, D S
Abstract : Introduction: Lymphocytic duodenosis (LD) is found in 2% of duodenal biopsies. LD is defined by normal villous architecture and intraepithelial lymphocytes (IELs) >25 per 100 enterocytes. This is more commonly recognised as modified Marsh grade 1 on histopathology reports. Such patients should not be diagnosed with coeliac disease, solely by histology, as previous retrospective studies have suggested other associations with LD. Aims: To prospectively study the aetiology of LD. Methods: One hundred and sixty five patients with LD were rigorously investigated for coeliac disease and other known associations of LD, by means of revisiting the patient's history and recent investigations, followed by a combination of gluten challenge, HLA typing, repeat coeliac serology & duodenal biopsies, and exclusion of infection/inflammatory bowel disease. Results: 127 female: 38 male, age range 17–83 years, median age 46 years. Coeliac disease was present in 21% of patients with LD. In the absence of a positive coeliac diagnosis, LD was most commonly associated with anti-inflammatory drugs (17%), H pylori (16%), gastrointestinal infections (7%), immune dysregulation (6%), inflammatory bowel disease (3%), and IgA deficiency (1%). Overall, there were 49 (30%) cases where no cause was found and the IEL count normalised in 35/49 (71%). Irritable bowel syndrome (IBS) was a clinical diagnosis in 30 of these 49 patients. All patients with coeliac disease were HLA DQ2 or DQ8 positive, compared to 55% of non-coeliacs (p value <0.0001). Patients with coeliac disease were significantly associated with positive endomysial and/or raised tissue transglutaminase antibodies (p<0.0001). There was no statistical difference in age, gender or baseline bloods (haematology/biochemistry/inflammatory markers) between the coeliac and non-coeliac group (p>0.05). Conclusion: This is the largest cohort of patients systematically investigated for a cause of their LD. A cause can be identified in up to 70% of cases, with coeliac disease, anti-inflammatory drugs and H pylori representing the majority of cases. In those with no apparent cause, there may be an association with IBS and the IEL count becomes normal on repeat biopsy in 71%. Competing interests: None declared.